Traumatic Brain Injury: The Silent Epidemic - Canavan, Neil (MD Conference Express, 2008)
Traumatic brain injury (TBI) has become the hallmark injury of both the Iraq and Afghanistan wars, and as compared with previous conflicts, the chances of surviving a TBI have greatly improved. However, the numbers of soldiers with TBIs, described as “staggering” by the media, believe the true scope of the problem. According to data from the Centers for Disease Control (2004) civilians sustain an estimated 1.4 million TBIs annually in the US, resulting in 50,000 fatalities, 235,000 hospitalizations, and 1.1 million patients who are treated and then released from the ER to an uncertain future.